The Growing Importance of Aquaculture: The Case of Norwegian Salmon - Audun Iversen; Frank Asche; Thomas Nyrud; Roy Robertsen; Bjørn Inge Bendiksen; Roberto Cárdenas‐Retamal; Silje Steinsbø (Reviews in Aquaculture, 2025)
While the rapid growth in global aquaculture production has made the industry a success story in terms of providing nutritious food, it is often criticized for its limited socioeconomic effects. While there is a burgeoning literature investigating socioeconomic impacts, this is a difficult topic due to limited data availability. In this paper, we will review the socioeconomic impacts of the Norwegian salmon aquaculture industry using economic impact analysis, focusing on two impact measures: employment and value added. In contrast to earlier studies, we will cover the whole supply chain from input suppliers to sales rather than focusing on one part of the chain and accounting for ripple effects in several rounds. This is highly important as there, in 2022, were 11,175 direct jobs in production, 8500 jobs in additional core activities related to processing and sales, and 38,000 jobs with different suppliers and service providers, for a total of 57,800 jobs in the industry. The production activities are highly dispersed geographically and mostly conducted in coastal communities. While this is also true for some types of services, the employment in the industry becomes more concentrated and moves toward larger communities and cities as one moves downstream or away from the core activities.